MOBILE LEARNING AND HUMANISTIC BUDDHISM: A LITERATURE REVIEW - Chew, Fong Peng; Hutagalung Fonny Dameaty; Chang, Yin Liang (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Following the explosion of information communication and technology (ICT), mobile has become one of the useful teaching aids in education and is known as m-learning. M-learning has many advantages over other information technologies, such as computers in teaching many subjects including Humanistic Buddhism. This article is a review of literature about the use of ICT in education, m-learning, humanistic Buddhism, and the use of m-learning in the learning of humanistic Buddhism. The study shows that this aspect is still rarely being explored but has great potential to expand the knowledge about humanistic Buddhism to Buddhists.